Mineralogy, morphology, and reaction kinetics of ureolytic bio-cementation in the presence of seawater ions and varying soil materials - Robert J. Burdalski; Bruna G. O. Ribeiro; Michael G. Gomez; Drew Gorman-Lewis (Scientific Reports, 2022)
Abstract Microbially-induced calcium carbonate precipitation (MICP) is a bio-cementation process that can improve the engineering properties of granular soils through the precipitation of calcium carbonate (CaCO3) minerals on soil particle surfaces and contacts. The technology has advanced rapidly as an environmentally conscious soil improvement method, however, our understanding of the effect of changes in field-representative environmental conditions on the physical and chemical properties of resulting precipitates has remained limited. An improved understanding of the effect of subsurface geochemical and soil conditions on process reaction kinetics and the morphology and mineralogy of bio-cementation may be critical towards enabling successful field-scale deployment of the technology and improving our understanding of the long-term chemical permanence of bio-cemented soils in different environments. In this study, thirty-five batch experiments were performed to specifically investigate the influence of seawater ions and varying soil materials on the mineralogy, morphology, and reaction kinetics of ureolytic bio-cementation. During experiments, differences in reaction kinetics were quantified to identify conditions inhibiting CaCO3 precipitation and ureolysis. Following experiments, scanning electron microscopy, x-ray diffraction, and chemical composition analyses were employed to quantify differences in mineralogical compositions and material morphology. Ions present in seawater and variations in soil materials were shown to significantly influence ureolytic activity and precipitate mineralogy and morphology, however, calcite remained the predominant CaCO3 polymorph in all experiments with relative percentages exceeding 80% by mass in all precipitates.